2010
DOI: 10.7589/0090-3558-46.2.379
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Enterica Subsp. Enterica in Cattle Egret (Bubulcus Ibis) Chicks From Central Texas: Prevalence, Serotypes, Pathogenicity, and Epizootic Potential

Abstract: ABSTRACT:Cattle Egrets have a worldwide distribution, feed in proximity to cattle and other domestic animals, and often nest in large colonies in urban woodlots. Over a 3-yr period, nestlings from five Cattle Egret colonies from Central Texas, USA, were surveyed for salmonellosis. Prevalence of infection ranged from 29% to 95%. Seventeen Salmonella enterica subsp. enterica serotypes were isolated, of which the 4,5,12:i-monophasic serotype predominated in cultures of both the digestive tract and pooled spleen a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…from wildlife is not uncommon, and prevalences similar to or higher than the 4.661.7% we observed have been reported for a range of avian, reptilian, and mammalian species (Quessy and Messier 1992;Handeland et al 2002;Renter et al 2006;Phalen et al 2010;Scheelings et al 2011). Six of the seven isolates in this study were identified as Salmonella Mississippi (Edwards et al 1943).…”
Section: Discussionsupporting
confidence: 85%
“…from wildlife is not uncommon, and prevalences similar to or higher than the 4.661.7% we observed have been reported for a range of avian, reptilian, and mammalian species (Quessy and Messier 1992;Handeland et al 2002;Renter et al 2006;Phalen et al 2010;Scheelings et al 2011). Six of the seven isolates in this study were identified as Salmonella Mississippi (Edwards et al 1943).…”
Section: Discussionsupporting
confidence: 85%
“…Salmonella species are food‐borne zoonotic pathogens of major public health concern, and leading to huge economic costs from animal losses and human illnesses throughout the world (Hilbert, Smulders, Chopra‐Dewasthaly, & Paulsen, ; Majowicz et al., ; Thorns, ; Wray & Wray, ). Wildlife can act as long‐term asymptomatic carriers of Salmonella , but this bacterium can also lead to mortality in weak individuals and cause outbreaks affecting large proportions of populations (Alley et al., ; Hall & Saito, ; Phalen et al., ; Refsum, Vikoren, Handeland, Kapperud, & Holstad, ). Negative effects in affected survivors include prominent and persistent gastroenteritis associated with intestinal inflammation and diarrhoea, infertility, as well as a negative impact on breeding success by effecting embryonic and neonatal mortality (Battisti, Giovanni, Agrimi, & Bozzano, ; Benskin, Wilson, Jones, & Hartley, ; Tizard, ).…”
Section: Introductionmentioning
confidence: 99%
“…During the non-breeding season, ibis forage throughout the day in urban parks but roost at night in trees above water, often in wetlands and golf courses [40]. Because ibis have high winter survival, and as Salmonella is only known to cause mortality in nestlings [41,42], we ignore natural and disease-induced mortality and assume a constant flock size, N. We assume no immunity after recovery, such that re-exposure leads to new infection. As Salmonella either colonizes the gastrointestinal (GI) tract or results in transitory shedding [36], we divide infected ibis into transiently shedding (I t ) and actively colonized (I a ) hosts, where I t shed for a shorter duration (i.e.…”
Section: Model Developmentmentioning
confidence: 99%